Antioxidant activity and metabolic profile changes in Poria cocos fermented by breast-milk-derived Limosilactobacillus reuteri HM-R28 - Li, Xiaojing; Li, Xianping; Liu, Lu; Zhao, Junying; Zhang, Yue; Chen, Lijun (Frontiers in Nutrition, 2025)
IntroductionThe fermentation of lactic acid bacteria can alter the nutraceutical and functional efficacy of food and medicinal products, particularly when involving bioactive compounds similar to those in Poria cocos (P. cocos), which include polysaccharides and triterpenoids. In this study, we used Limosilactobacillus reuteri HM-R28 (L. reuteri HM-R28) from breast milk to ferment P. cocos in a liquid state and investigated changes in the physicochemical properties and metabolic composition before and after fermentation.MethodsAdditionally, we evaluated the effect of L. reuteri HM-R28 on the antioxidant activity and polysaccharide content of the P. cocos fermentation broth to elucidate its role.Results and discussionFermentation with L. reuteri HM-R28 enhanced the antioxidant activity of the fermentation solution. Liquid fermentation significantly altered the metabolites of P. cocos. Based on the broadly targeted metabolomics analysis, a total of 549 differential metabolites were detected in the fermentation broth before and after fermentation, with 254 metabolites significantly upregulated and 295 metabolites significantly downregulated. These differential metabolites were associated with 41 metabolic pathways, primarily involving lipids and lipid constituents, organic acids and their derivatives, and heterocyclic organic compounds. Liquid fermentation also increased antioxidant compounds such as sedanolide, pomegranate acid, and epigallocatechin, along with aromatic volatile substances such as delta-tridecanolactone, γ-nonanolactone, and 3-acetyl-2, 5-dimethylfuran. These insights establish a conceptual framework for advancing the use of human milk-derived lactic acid bacteria for fermenting medicinal and edible homologous products. To our knowledge, this is the first study to elucidate the role of human milk-derived probiotics in enhancing the bioactive compounds of P. cocos through fermentation. Our findings can provide a theoretical foundation for the development of medicinal and edible homologous products fermented with human milk-derived Lactobacillus strains.